Unravelling axonal transcriptional landscapes: insights from induced pluripotent stem cell-derived cortical neurons and implications for motor neuron degeneration - Jishu Xu; Michaela Hörner; Maike Nagel; Perwin Perhat; Milena Korneck; Marvin Noß; Stefan Hauser; Ludger Schoels; Jakob Admard; Nicolas Casadei; Rebecca Schuele (Open Biology)
Neuronal function and pathology are deeply influenced by the distinct molecular profiles of the axon and soma. Traditional studies have often overlooked these differences due to the technical challenges of compartment-specific analysis. In this study, we employ a robust RNA-sequencing approach, using microfluidic devices, to generate high-quality axonal transcriptomes from induced pluripotent stem cells-derived cortical neurons (CNs). We achieve high specificity of axonal fractions, ensuring sample purity without contamination. Comparative analysis revealed a unique and specific transcriptional landscape in axonal compartments, characterized by diverse transcript types, including protein-coding mRNAs, RNAs encoding ribosomal proteins, mitochondrial-encoded RNAs and long non-coding RNAs. Previous works have reported the existence of transcription factors (TFs) in the axon. Here, we detect a set of TFs specific to the axon and indicative of their active participation in transcriptional regulation. To investigate transcripts and pathways essential for central motor neuron (MN) degeneration and maintenance we analysed kinesin family member 1C (KIF1C)-knockout (KO) CNs, modelling hereditary spastic paraplegia, a disorder associated with prominent length-dependent degeneration of central MN axons. We found that several key factors crucial for survival and health were absent in KIF1C-KO axons, highlighting a possible role of these also in other neurodegenerative diseases. Taken together, this study underscores the utility of microfluidic devices in studying compartment-specific transcriptomics in human neuronal models and reveals complex molecular dynamics of axonal biology. The impact of KIF1C on the axonal transcriptome not only deepens our understanding of MN diseases but also presents a promising avenue for exploration of compartment-specific disease mechanisms.